2017
DOI: 10.1093/nar/gkx196
|View full text |Cite
|
Sign up to set email alerts
|

NMR-based method of small changes reveals how DNA mutator APOBEC3A interacts with its single-stranded DNA substrate

Abstract: APOBEC3 proteins are double-edged swords. They deaminate cytosine to uracil in single-stranded DNA and provide protection, as part of our innate immune system, against viruses and retrotransposons, but they are also involved in cancer evolution and development of drug resistance. We report a solution-state model of APOBEC3A interaction with its single-stranded DNA substrate obtained with the ‘method of small changes’. This method compares pairwise the 2D 15N–1H NMR spectra of APOBEC3A bearing a deactivating mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 48 publications
6
28
2
Order By: Relevance
“…It remains to be determined whether increased fl A3B activity is due to different catalytic pocket accessibility in the fl A3B than A3B CTD, if the NTD of A3B is better able to guide the ssDNA substrate into the catalytic pocket, if increased processivity enables a more efficient search for potential deamination motifs, or a combination of all of these factors. Recently, it has been shown that A3A and A3B CTD bend the ssDNA substrate in the active site ( 37 , 98 , 99 ). How this relates to processivity and if the enzymes can induce the ssDNA bending of larger substrates, such as dynamic ssDNA exposed during replication or transcription remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be determined whether increased fl A3B activity is due to different catalytic pocket accessibility in the fl A3B than A3B CTD, if the NTD of A3B is better able to guide the ssDNA substrate into the catalytic pocket, if increased processivity enables a more efficient search for potential deamination motifs, or a combination of all of these factors. Recently, it has been shown that A3A and A3B CTD bend the ssDNA substrate in the active site ( 37 , 98 , 99 ). How this relates to processivity and if the enzymes can induce the ssDNA bending of larger substrates, such as dynamic ssDNA exposed during replication or transcription remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the fluctuation of the positions of residues about their mean position (root mean squared fluctuation [RMSF]) over three independent 1 μs MD trajectories shows three highly flexible regions in A3Bctd (Fig. 4B ): the loop 1 region spanning residues Asn204 to Gln213, the loop following β1 and the first half of the interrupted β2 (including Asp224 to Met231 which are disordered in the new crystal form), and the loop 3 region truncated in our crystal structures but shown to be highly flexible in NMR studies of A3Bctd and A3A 33 35 . Wild-type A3A MD simulations also showed high mobility of the latter two regions, however, A3A loop 1 had limited flexibility compared to the corresponding loop 1 region of A3Bctd (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The overall U-shaped conformation of A3A ssDNA substrate has been corroborated by a 2D- 15 N-HSQC NMR analysis of A3A (E72A) titrated with a series of ssDNA substrates that differ by a single nucleotide [80] . This ‘method of small changes’ allows for more precise assignment of chemical shift peaks and thus more informed modeling of bound ssDNA.…”
Section: An A3 Ssdna Substrate Has An Unexpected U-shaped Orientationmentioning
confidence: 83%